Painting & the market in early modern Antwerp - Honig, Elizabeth Alice 1960- (Yale University Press, 1998)
Honig discusses the paintings of Pieter Aertsen and his nephew Joachim Beuckelaer within the context of a developing aesthetic of exchange, as art became increasingly defined as an alluring commodity that aroused in its beholder a desire for possession and called upon the tempering forces of individual reason and self-judgment. She then examines the relation between painting and the market that emerged in Antwerp after the Spanish reconquest, a period of social, economic, and religious retrenchment
Keywords: Geschichte 1600-1700; Geschichte 1500-1600; Geschichte 1550-1650; Geschichte 1500-1700; Art - Commerce - Belgique - Anvers (Belgique) - 1500-1800; Art et société - Belgique - Anvers - Histoire - 16e siècle; Art et société - Belgique - Anvers - Histoire - 17e siècle; Economische geschiedenis; Marchés - Dans l'art; Markten; Painting - 16th century - Belgium - Antwerp; Painting - 17th century - Belgium - Antwerp; Peinture - Belgique - Anvers (Belgique) - 16e siècle; Peinture - Belgique - Anvers (Belgique) - 17e siècle; Peinture - Belgique - Anvers - 16e siècle; Peinture - Belgique - Anvers - 17e siècle; Peinture - Belgique - Anvers - Commercialisation; Schilderkunst; Geschichte; Kunst; Malerei; Art and society -- Belgium -- Antwerp -- History -- 16th century; Art and society -- Belgium -- Antwerp -- History -- 17th century; Painting -- 16th century; Painting -- Belgium -- Antwerp -- Marketing; Painting, Modern -- 17th century; Values -- Belgium -- Antwerp; Kunstmarkt; Kunstsoziologie; Kunstbetrieb; Belgien; Antwerpen; Flandern